Evaluation of biology practicum implementation: Analysis of achievement of science process skills, literacy numeracy and conceptual understanding - St. Syahirah; Bambang Supriatno; Nuryani Rustaman (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2025)
Science process skills (SPS) are fundamental for 21st-century education, as they foster students’ reasoning, inquiry competence, and conceptual understanding. In biology learning, SPS play a central role in cultivating scientific literacy and preparing students with critical thinking and problem-solving abilities required in the global era. Yet, international assessments such as PISA consistently show that Indonesian students perform below the OECD average in scientific literacy, indicating weaknesses in evidence-based reasoning and application of scientific concepts. This problem is often linked to teacher-centered instruction and limited implementation of inquiry-based laboratory activities in schools. This study investigates the implementation of SPS in biology practicum through interviews with teachers and analysis of laboratory activity documents from five public senior high schools in Makassar. A qualitative descriptive method was applied, focusing on indicators such as observation, classification, prediction, data interpretation, hypothesis formulation, experimental planning, communication, and concept application. The results reveal that observation and interpretation are partially practiced but lack structured guidance and do not encourage student autonomy. Other skills, including classification, prediction, hypothesis formulation, experimental planning, and communication, are rarely emphasized because students mostly follow predetermined procedures. The findings conclude that biology practicum has not effectively supported SPS development, reinforcing students’ low scientific literacy. Strengthening inquiry-based learning and enhancing teacher professional development are recommended to improve laboratory pedagogy and foster meaningful, student-centered science learning.Abstrak. Keterampilan proses sains (KPS) merupakan aspek fundamental dalam pendidikan abad ke-21 karena berperan penting dalam menumbuhkan penalaran, kompetensi inkuiri, dan pemahaman konsep peserta didik. Dalam pembelajaran biologi, KPS menjadi kunci untuk mengembangkan literasi sains sekaligus mempersiapkan siswa dengan kemampuan berpikir kritis dan pemecahan masalah yang dibutuhkan pada era global. Namun, asesmen internasional PISA secara konsisten menunjukkan bahwa capaian literasi sains siswa Indonesia berada di bawah rata-rata OECD, yang mencerminkan kelemahan dalam penalaran berbasis bukti dan penerapan konsep ilmiah. Kondisi ini sering dikaitkan dengan pembelajaran berpusat pada guru serta keterbatasan penerapan praktikum berbasis inkuiri di sekolah. Penelitian ini bertujuan untuk mengeksplorasi implementasi KPS dalam kegiatan praktikum biologi melalui analisis wawancara dengan guru biologi dan dokumen kegiatan laboratorium (DKL) di lima sekolah menengah atas negeri di Makassar. Penelitian menggunakan metode deskriptif kualitatif dengan fokus pada kelengkapan dan kedalaman indikator KPS, seperti mengamati, mengklasifikasi, memprediksi, menafsirkan data, merumuskan hipotesis, merancang eksperimen, mengomunikasikan, dan menerapkan konsep. Hasil menunjukkan bahwa keterampilan mengamati dan menafsirkan sudah diterapkan namun belum terstruktur dan kurang mendorong kemandirian siswa. Sementara itu, keterampilan lain seperti klasifikasi, prediksi, dan perumusan hipotesis masih jarang dilatihkan. Perencanaan eksperimen dan komunikasi ilmiah juga terbatas karena siswa hanya mengikuti prosedur yang tersedia. Disimpulkan bahwa pendekatan praktikum saat ini belum mendukung pengembangan KPS secara menyeluruh. Diperlukan penerapan model pembelajaran berbasis inkuiri serta pelatihan profesional guru untuk meningkatkan pedagogi laboratorium dan pembelajaran yang berorientasi pada siswa.